Comparative Analysis of Voice Call Service Quality Between CSFB and VoLTE Technologies - Aqrizal, M. Aqsha (Politeknik Negeri Padang, 2025)
This study examines the performance of voice services using CSFB and VoLTE technologies. The quality of these services is evaluated using Key Performance Indicators (KPIs) from Drive Test results and key Quality of Service (QoS) metrics. Voice service quality is assessed through drive testing with Tems Pocket software. The findings reveal that CSFB technology involves a transition in Radio Access Technology (RAT) from LTE to GSM, whereas VoLTE operates without such transitions. In Indonesia, voice services without data primarily rely on both CSFB and VoLTE. The quality of these services is determined by factors such as RSRP and SINR, which affect the service’s accessibility, retention, and integrity. VoLTE, in particular, outperforms CSFB in terms of better throughput and reduced delay, enhancing overall service integrity.